Pandangan Tokoh NU Tentang Hadirnya Wali yang Telah Mewakilkan Perwaliannya - M. Zaenal Abidin; Nurul Azizah (Program Pascasarjana Universitas Ibrahimy, 2017)
It has become the custom people when they want to marry their children so the guardian represents either to the kiai, ustad, or penghulu on the grounds, the guardian isn’t confident to marry himself because he or she hopes to be barokah from someone who is considered more appropriate to do. After the guardian surrender his guardianship to the deputy, the guardian is usually asked to leave when the contract is executed without apparent reason. The purpose of study is to know how the views of NU Jember figures about the presence of a guardian has represented his guardianship in majlis akad and how the view of Islamic legal opinion about the presence of a guardian has represented his it. The approach method used research is qualitative approach, the data collection technique chosen is interview. The results of research found in addressing of NU jember character different views. Some NU leaders have some opinions that a guardian has represented his or her guardianship may be present in the contracting majlis and hasn’t effect the contract carried out as long as it doesn’t become one of the witnesses of the marriage.